An Innocent Appearing Subcutaneous Nodule Diagnoses a Small Cell Lung Cancer in a Never-Smoker Female. (10th March 2014) - Sinha, Nupur; Niazi, Masooma; Diaz-Fuentes, Gilda; Duncalf, Richard
Abstract : Lung cancer among never-smokers is recognized as the 7th most common cause of cancer death globally. Adenocarcinoma is the most commonly reported histology. Small cell lung cancer (SCLC) has the strongest association with smoking and is rarely reported in never-smokers. Although lung cancer in never-smokers is more common in women, the overall incidence of SCLC in female never-smokers still remains low. Soft tissue metastases from any cancer are rare with an overall prevalence of 1.8%. Soft tissue metastases from lung primary are uncommon, mostly from adenocarcinoma, and portend a poor prognosis. Cutaneous metastases from SCLC are exceptionally rare with reported incidence of 0.3% to 0.8%. We believe ours is the first reported case of SCLC presenting as subcutaneous nodule, in a never-smoker, otherwise asymptomatic female. The diagnosis of SCLC was made incidentally by the excisional biopsy of the subcutaneous nodule. Subsequent CT chest and PET scan revealed a hypermetabolic right lower lobe spiculated lung mass with adrenal and liver involvement. Platinum and etoposide chemotherapy with prophylactic cranial irradiation was initiated for advanced SCLC, and she required further irinotecan and taxol for subsequent pancreatic and adrenal metastases. With continued deterioration, she died approximately 36 months from diagnosis, while under hospice care.